Spermatid-specific linker histone HILS1 is a poor condenser of DNA and chromatin and preferentially associates with LINE-1 elements - Mishra, Laxmi Narayan (Epigenetics Chromatin, 2018)
BACKGROUND: Linker histones establish and maintain higher-order chromatin structure. Eleven linker histone subtypes have been reported in mammals. HILS1 is a spermatid-specific linker histone, and its expression overlaps with the histone–protamine exchange process during mammalian spermiogenesis. However, the role of HILS1 in spermatid chromatin remodeling is largely unknown. RESULTS: In this study, we demonstrate using circular dichroism spectroscopy that HILS1 is a poor condenser of DNA and chromatin compared to somatic linker histone H1d. Genome-wide occupancy study in elongating/condensing spermatids revealed the preferential binding of HILS1 to the LINE-1 (L1) elements within the intergenic and intronic regions of rat spermatid genome. We observed specific enrichment of the histone PTMs like H3K9me3, H4K20me3 and H4 acetylation marks (H4K5ac and H4K12ac) in the HILS1-bound chromatin complex, whereas H3K4me3 and H3K27me3 marks were absent. CONCLUSIONS: HILS1 possesses significantly lower α-helicity compared to other linker histones such as H1t and H1d. Interestingly, in contrast to the somatic histone variant H1d, HILS1 is a poor condenser of chromatin which demonstrate the idea that this particular linker histone variant may have distinct role in histone to protamine replacement. Based on HILS1 ChIP-seq analysis of elongating/condensing spermatids, we speculate that HILS1 may provide a platform for the structural transitions and forms the higher-order chromatin structures encompassing LINE-1 elements during spermiogenesis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13072-018-0214-0) contains supplementary material, which is available to authorized users.